2007
DOI: 10.1096/fj.07-8276com
|View full text |Cite
|
Sign up to set email alerts
|

EGF regulates plasminogen activator inhibitor‐1 (PAI‐1) by a pathway involving c‐Src, PKCδ, and sphingosine kinase 1 in glioblastoma cells

Abstract: Patients with gliomas expressing high levels of epidermal growth factor receptor (EGFR) and plasminogen activator inhibitor-1 (PAI-1) have a shorter overall survival prognosis. Moreover, EGF enhances PAI-1 expression in glioma cells. Although multiple known signaling cascades are activated by EGF in glioma cells, we show for the first time that EGF enhances expression of PAI-1 via sequential activation of c-Src, protein kinase C delta (PKCdelta), and sphingosine kinase 1 (SphK1), the enzyme that produces sphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
60
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 46 publications
6
60
1
1
Order By: Relevance
“…The present in vitro data demonstrate that a IL-6 and PAI-1 co-expression in epithelial ovarian cancer C Alberti et al signaling cascade from ligand-stimulated EGFR/MEK/ ERK or EGFR/PI3K/AKT activates the transcriptional activity of NFkB with expression of IL-6 together with PAI-1. A similar signaling pathway has been experimentally demonstrated in glioblastoma cell lines (Paugh et al, 2008), and a positive correlation between PAI-1 and IL-6 gene expression has been observed in a metaanalysis carried out on publicly available data sets of gene expression of breast carcinoma (Sternlicht et al, 2006). Interestingly, very recently ErbB2 expression, another member of the ErbB family, was found to upregulate IL-6 production through the transcriptional activity of NFkB (Hartman et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…The present in vitro data demonstrate that a IL-6 and PAI-1 co-expression in epithelial ovarian cancer C Alberti et al signaling cascade from ligand-stimulated EGFR/MEK/ ERK or EGFR/PI3K/AKT activates the transcriptional activity of NFkB with expression of IL-6 together with PAI-1. A similar signaling pathway has been experimentally demonstrated in glioblastoma cell lines (Paugh et al, 2008), and a positive correlation between PAI-1 and IL-6 gene expression has been observed in a metaanalysis carried out on publicly available data sets of gene expression of breast carcinoma (Sternlicht et al, 2006). Interestingly, very recently ErbB2 expression, another member of the ErbB family, was found to upregulate IL-6 production through the transcriptional activity of NFkB (Hartman et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with this conclusion is our observation and that of others of the synergism between TGF␤ and growth factors that stimulate the MAPK pathway (44,45). Protein kinase C can also activate the MAPK pathway, and in glioma cells, PKC␦ is activated by EGF via Src (46). However, in this study, we found that inhibiting Src did not prevent synergism between EGF and TGF␤.…”
Section: Discussionsupporting
confidence: 92%
“…EGF, just like HA, induces expression of PAI-1 by PKC delta in glioblastoma cells (Paugh et al, 2008). TNF-α regulates TGFβ-promoted epithelial mesenchymal transition (EMT) by inducing HA-CD44-moesin interaction (Takahashi et al, 2010), suggesting transactivation of TGFβRI by TNF-α.…”
Section: Discussionmentioning
confidence: 99%